TANGGUNG JAWAB DIREKSI ATAS LAPORAN KEUANGAN PERUSAHAAN PUBLIK - Rumata Rosininta Sianya; Bismar Nasution; Ningrum Natasya Sirait; Sunarmi Sunarmi (USU LAW JOURNAL, 2018)
ABSTRACT One of the organs of a company is Board of Directors that are fully responsible for the management, interest, and goals of a company and representing the company either in or outside of court of law (persona standi in judicio). Public company with applies the principle of transparency requiring the Board of Directors to periodically provide a financial report to Badan Pengawas Pasar Modal (Bapepam) as regulated in the Regulation of Bapepam No. VIII.G.7. Board of Directors of Public Company are required to issue a Letter of Responsibility of Board of Directors for the Financial Report signed by President Director and Financial Director. If an information /material fact inflicting loss to the third party is found in the financial report, according to Law on Limited Liability Company and the Regulation of Bapepam No. VIII.G.7, the Board of Directors of Public Company is jointly and severally reponsible for the injured parties. Therefore, the writer is interested in doing a study entitled “The Responsibility of Board of Directors for the Financial report of Public Company”. The criteria determining whether or not the Board of Directors made an offense in terms of signing a statement stating the responsibility of Board of Directors for the financial report inflicting loss to the party outside of the company can be seen from the substance of the financial report whether or not it was made under good faith and full of responsibility for the proper purpose of the company, whether or not the Board of Directors had applied the standard of care that they were avoided from negligence that can inflicting loss to other parties, whether or not the Board of Directors had been beyond their authority, not only to what is prohibited in the statutes of the company but also to the existing regulations or public order (ultra vires), and whether or not the Board of Directors made their business decision based on rational basis. The form of the responsibility of the Board of Directors for the financial report according to the Law on Limited Liability Company and the Regulation of Bapepam No. VIII.G.7 in the case of incorrect or misleading information/material fact inflicting loss to other parties was a joint responsibility off all members of the Board of Directors of the public company because whether or not the substance of the letter of statement of the Board of Directors related to the financial report was correct, was binding and become juridical responsibility of all members of the Board of Directors of public company, considering that President Director and Financial Director signing the financial report acted for and on behalf of the company as long as the principles of duty of care, good faith and rational basis in drafting and preparing the financial report were applied by the President Director and Financial Director, all of the members of the Board of Directors are required to have a joint responsibility for the loss inflicted to the third party. Keywords: Responsibility, Financial Report, Public Company